Register Usage in K-Pop Fan Communities on Social Media X: An Analysis of Heart2Hearts Indonesia Fanbase - Malida, Alya; Sulistyowati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to examine the form and function of registers used in the Heart2Hearts Indonesia fanbase account on social media X by the K-pop fan community, especially the Hatchu (S2U) fandom. The research uses a qualitative approach with observation and documentation methods as data collection techniques. Data in the form of utterances containing registers were classified based on lingual forms (words, phrases, sentences, abbreviations, and acronyms) and analyzed based on the context of meaning and language function using Halliday's theory. The analysis shows that out of 72 lingual data, phrase is the most dominant form used, which is 43 data or 59.72%. Followed by words as much as 12 data (16.67%), sentences as much as 7 data (9.72%), and abbreviations and acronyms each as much as 5 data (6.94%). The dominance of phrases shows the community's tendency to use syntactic structures that are dense in meaning but do not form complete sentences. In terms of language function, of the 78 data analyzed, it was found that the personal function was the most dominant with 39.08%, followed by the representational function at 32.18%. The interactional function accounts for 10.34% and the regulative function for 5.75%. Meanwhile, instrumental and heuristic functions only account for 1.15% each. These results show that language use in fan communities tends to be used to express personal feelings and convey information, with social and directional functions as complements. Thus, it can be concluded that phrasal forms and personal functions characterize the communication patterns of K-pop fan communities on social media, reflecting the expressive, meaning-dense, and interactive characteristics of language.